COVID - 19: Clinical Profile and Outcome of Patients from Tertiary Care Center in North India - S. R. Manjunath; Ravishekar N. Hiremath; Kasi Vishwanath; S. K. Thakur; S. K. Choudhary; Sandhya Ghodke (Current Overview on Disease and Health Research Vol. 7, 2023)
An acute respiratory infection of unknown origin was first identified in Wuhan, china and reported to WHO on 31st December 2019 and within a month, this outbreak was declared as a Public Health Emergency of International Concern. This chapter aims to to assess the spectrum of clinical presentations and host related factors in outcome of COVID-19 during the first wave. This single centre study revealed the range of clinical manifestations and host-related characteristics in COVID-19’s first wave outcomes, which may help in decrease the burden of disease, minimize social disruption, and reduce the economic impact associated with a pandemic. Early recognition, admission, and treatment of older and co-morbid patients might hasten the recovery from the illness and hence lower mortality.